Improved Radioimmunodetection of Carcinomas with a Re-injection of Monoclonal Antibodies after Formation of Anti-mouse Antibodies - Werner, Felix-Martin; Covenas, Rafael (Current Pharmaceutical Design, 2023)
Scintigraphic imaging was satisfactory in animal experiments, i.e., in the radioimmunodetection with 125J anti-tissue polypeptide antigen monoclonal antibodies and implanted HELA cell carcinomas. Unlabeled anti- mouse antibodies (AMAB), in a surplus of 40:1, 200:1 and 4000:1 compared to the radioactive antibody, were administered five days after administering the 125I anti-TPA antibody (RAAB). In immunoscintigraphies, radioactivity accumulated in the liver immediately after administering the secondary antibody, and the tumor's imaging worsened. It can be expected that imunoscintigraphic imaging might improve when radioimmunodetection is re-performed after the formation of human anti-mouse antibodies (AMAB) and when the ratio of the primary to the secondary antibody is nearly equivalent because, in this ratio, the formation of immune complexes might be accelerated. It is possible to measure the quantity of formed anti-mouse antibodies (AMAB) with immunography measurements. A second administration of diagnostic or therapeutic monoclonal antibodies might lead to the formation of immune complexes if the quantities of the monoclonal antibodies and the anti-mouse antibodies have an equivalent ratio. A second performance of the radioimmunodetection four to eight weeks after the first radioimmunodetection can achieve better tumor imaging because human anti-mouse antibodies (AMAB) can be formed. Immune complexes of the radioactive antibody and the human anti-mouse antibody (AMAB) can be formed to concentrate radioactivity in the tumor.
Keywords: RAAB